Ответы 3

  • спасибо!
  • Удачи.
  • (4x-3)⁴-34*(4x-3)²-72≤0

    Пусть (4x-3)²=t   ⇒

    t²-34t-72≤0

    t²-34t-72=0       D=1444       √D=38

    t₁=(4x-3)²=-2      

    t₂=(4x-3)²=36  

    16x²-24x+9=36

    16x²-24x-27=0    D=2304     √D=48

    x₁=2,25     x₂=-0,75

    (4x-3)²+2)(x+0,75)(x-2,25)≤0

    (4x-3)²+2)>0    ⇒

    (x+0,75)(x-2,25)≤0

    -∞__+__-0,75__-__2,25__+__+∞

    Отввет: x∈[-0,75;2,25].

    • Автор:

      rustymjup
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years